Modification of frictional surfaces of bearings by addition of nanoparticle compositions to lubricants - Lyubchenko, Olena; Gapochenko, Svitlana (Національний технічний університет "Харківський політехнічний інститут", 2024)
The results of a study of the effect of additives to lubricating oils on changes in the structure of the friction surface and, as a consequence, the tribological characteristics of the "steel to steel" friction pair are presented. The experiments were conducted using a standard "disk-disk" scheme on a friction machine with double cycles of step loading. The material of the disks was bearing steel ШХ-15 with a hardness of 61-63 HRC. Changes in the surface structure were monitored using a binocular microscope. A detailed study of the friction surfaces was carried out using a scanning electron microscope. The microhardness of the friction surfaces was also measured before and after loading. Quantitative changes in the surface relief were determined using a profilometer. The study of the friction surface, conducted using X-ray fluorescence analysis, revealed changes in the composition of the surface layer, which can be explained by the formation of a surface servovite film, which includes elements from the used additive to lubricant (silicon, magnesium, manganese, aluminum, sulfur). The increase in the microhardness of the friction surface when working with the additive from 4.1 GPa to 6.6 GPa, which has a positive effect on the tribological characteristics, is also explained by the formation of a servovite film, which can significantly improve the friction conditions, as well as reduce damage and wear of surfaces. Using scanning electron microscopy, surface waviness oriented at large angles (close to the normal) to the direction of deformation during friction was revealed. It was assumed that the reason for the formation of such a surface relief is microplastic deformation under the action of bias stresses arising in the surface layers of the friction pair. The structural changes observed during friction with the use of a lubricant additive support the assumption of the formation of a ceramic (servovite) film, which has a significantly greater reserve of plasticity compared to a surface with an oxide film, usually present on the surface during friction with a lubricant without an additive.

Надані результати дослідження впливу присадок до мастил на зміну структури поверхні тертя і, як наслідок, трибологічних характеристик пари тертя «сталь - сталь». Експерименти проводилися з використанням стандартної схеми «диск-диск» на машині тертя при двократних циклах ступінчастого навантаження. Матеріалом дисків була підшипникова сталь ШХ-15 твердістю 61-63 HRC. Зміни структури поверхні контролювали за допомогою бінокулярного мікроскопа. Детальне дослідження поверхонь тертя проводилося за допомогою растрового електронного мікроскопа. Також вимірювалася мікротвердість поверхонь тертя до та після навантаження. Кількісні зміни поверхневого рельєфу визначалися за допомогою профілометра. Вивчення поверхні тертя, виконане за допомогою рентгенівського флуоресцентного аналізу, дозволило виявити зміни у складі поверхневого шару, яка може бути пояснена утворенням поверхневої сервовітної плівки, до складу якої входять елементи з добавки до мастила (кремній, магній, марганець, алюміній, сірка). Збільшення мікротвердості поверхні тертя при роботі з добавкою з 4.1 ГПа до 6,6 ГПа, що позитивно позначається на трибологічних характеристиках, також пояснюється утворенням сервовітної плівки, яка дозволяє суттєво покращити умови тертя, а також зменшити пошкодження та зношування поверхонь. За допомогою растрової електронної мікроскопії було виявлено поверхневу хвилястість, орієнтовану під великими кутами (близькими до нормалі) до напрямку деформації при терті. Було припущено, що причиною формування такого поверхневого рельєфу є мікропластична деформація під дією зсуву напруги, що виникає в поверхневих шарах пари тертя. Зміни структури, які виявляються при терті з використанням добавки до мастила, підтверджують припущення про утворення керамічної (сервовітної) плівки, яка має значно більший запас пластичності порівняно з поверхнею з оксидною плівкою, яка зазвичай присутня на поверхні при терті з мастилом без присадки.
Модифікація фрикційних поверхонь підшипників шляхом додавання композицій наночастинок до мастил
Keywords: grease; surface structure; coefficient of friction; wear; nanoparticles; surfaces of bearings; поверхні підшипників; наночастинки; мастила; структура поверхні; коефіцієнт тертя; керамічна плівка